The Role of Echocardiography in Community-Based Health Campaigns: A Cross-Sectional Experience - Alsrur, Alsrur; Hamoud H, Hamad (Journal of Neonatal Surgery, 2025)
Background: Transthoracic echocardiography (TTE) is a non-invasive, widely available diagnostic tool for cardiovascular assessment. Its utility in community screening, especially in resource-limited settings, remains underexplored. Objective: To assess the feasibility, echocardiographic findings, and clinical impact of portable TTE during community-based health campaigns in Hail, Saudi Arabia. Methods: This cross-sectional study was conducted involving 100 adult participants (≥18 years) screened in public areas using portable echocardiography. Basic parameters including LVEF, LVMI, and wall thicknesses were measured. Participants were categorized into normal, follow-up, or referred based on findings. Results: The mean age was 48.9±11.6 years; 81% were male. Most participants (71%) had normal echocardiograms, while 29% showed abnormalities. Valvular dysfunction (12%), left ventricular hypertrophy (6%), and reduced LVEF (<50%) (4%) were the most common findings. Significant congenital conditions such as VSD and bicuspid aortic valve were detected in 1% each. Among those with abnormal findings, 15% were referred for further care, and 14% advised follow-up. Age, BMI, and comorbidities (particularly DM+HTN) were strong predictors of abnormal findings (p<0.01). Conclusion: Community-based echocardiographic screening using portable devices is feasible and valuable in detecting subclinical cardiac disease. It enables early identification and referral in underserved populations. Targeting high-risk groups such as older adults and those with chronic diseases can enhance screening efficiency